Non mechanical traumatic gas gangrene: forgotten but not gone - Subramanian Senthilkumaran; Ritesh G. Menezes; Sadip Pant; Namasivayam Balamurugan; Ponniah Thirumalaikolundusubramanian (Mediterranean Journal of Hematology and Infectious Diseases)
We report a case of gas gangrene in a non diabetic HIV sero negative young male who succumbed to death within 60 hours following an intramuscular injection in rural India. Occurrence of GG after intramuscular injection is rare and only a few cases has been reported so far in the literature